1987
DOI: 10.1083/jcb.104.6.1683
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of small dermatan sulfate proteoglycan from fibroblasts with fibronectin.

Abstract: Abstract. Immunogold labeling was used to localize the core protein of small dermatan sulfate proteoglycan (DS-PG) on the surface of cultured human fibroblasts. At 4°C, DS-PG core protein was uniformly distributed over the cell surface. At 37°C, gold particles either became rearranged in form of clusters or remained associated with fibrils. Double-label immunocytochemistry indicated the co-distribution of DS-PG core protein and fibronectin in the fibrils. In an enzyme-linked immunosorbent assay, binding of DS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
1
4

Year Published

1989
1989
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(99 citation statements)
references
References 62 publications
(60 reference statements)
0
94
1
4
Order By: Relevance
“…Chromogen was formed by incubation with 3 mM 4-chloro-l-naphtol in buffer B containing 0.003% H,O, and 17% (v/v) methanol. For staining with MAb against decorin (25). peroxidaseconjugated goat anti-mouse IgG was used in a 1 : 500 dilution.…”
Section: Methodsmentioning
confidence: 99%
“…Chromogen was formed by incubation with 3 mM 4-chloro-l-naphtol in buffer B containing 0.003% H,O, and 17% (v/v) methanol. For staining with MAb against decorin (25). peroxidaseconjugated goat anti-mouse IgG was used in a 1 : 500 dilution.…”
Section: Methodsmentioning
confidence: 99%
“…Extracellular matrix (ECM) proteins under TGF-␤ regulation include collagens, decorin, and fibronectin (Balza et al, 1988;Saed et al, 1999;Klein et al, 2002;Fu et al, 2005). Both decorin and fibronectin are capable of binding TGF-␤, presumably to regulate its activity (Schmidt et al, 1987;Mooradian et al, 1989;Yamaguchi et al, 1990;Hildebrand et al, 1994;Schonherr et al, 1998). Decorin, in particular, has been shown to possess independent binding sites for TGF-␤s and collagen type I (Schonherr et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The core protein of decorin interacts with several matrix proteins, such as collagens (51)(52)(53)(54)(55), fibronectin (14,56), and thrombospondin (15). Decorin has been visualized at the ultrastructural level bound at the d band of fibrillar collagen (10) and in association with fibronectin fibrils at the surface of cells (57). Studies of in vitro fibrillogenesis have shown that the interaction of decorin with collagen regulates the rate of collagen fibrillogenesis as well as fibril size and interfibrillar spacing (11,12,58,59).…”
Section: Fig 7 Immunofluorescent Staining For Fibronectin In Vectormentioning
confidence: 99%